Pemberdayaan Perempuan melalui Seminar dan Pelatihan Berkebaya sebagai Upaya Penguatan Peran Keluarga dan Pelestarian Budaya - Elis Sondang Dasawati; Siti Meisyaroh; Martha Ayerza Esra (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
Women's emancipation is a frequently discussed topic today. Women are beginning to appear in all fields of work, from jobs requiring higher education such as engineering, medicine, economics, and piloting, to jobs often held by men because they are considered to require strong physical strength, such as security guards, drivers, and cleaners. Therefore, it is interesting to discuss how women can empower their families, communities, and uphold national culture. This community service activity aims to provide information and knowledge to Pemberdayaan Kesejahteraan Keluarga (PKK) mothers who are interested in gaining insight into the role of women in the family and community in developing and preserving national culture. This training and presentation are part of a community service program for lecturers at the Kwik Kian Gie Institute of Business and Informatics and are conducted in collaboration with the PKK mothers of RW 16 Grand Prima Bintara Bekasi. It is hoped that this activity will not end with today's seminar but will continue in the next seminar